Francesco Petrarca travelling and writing to Prague’s court - Špička, Jiří (Verbum – Analecta Neolatina, 2010)
This paper deals with the cultural and political contacts between Francesco Petrarca and the imperial court in Prague. Leaving aside the political motivation of the epistolary exchange between Petrarca and the Emperor Charles IV, we firstly focus on the history of Petrarca’s journey(s) to Prague as a curious experience in his life, and secondly on the nature of the "friendship" between Petrarca and the imperial chancellor Jan ze Středy, which we interpret as an obstinate and idle endeavour of self-promotion.